Analisis Yuridis terhadap Keabsahan Letter Of Credit sebagai Instrumen Pembayaran dalam Transaksi Ekspor-Impor di Indonesia - Berlianityaputri Ramadhanty Choirunnisa; Thifal Anjani (CV Rewang Rencang, 2025)
Letter of Credit, often referred to as L/C, is one of the internationally recognized methods of payment in Indonesia. An L/C is a document that contains a guarantee from a bank, indicating that the buyer will fulfill the payment obligations as agreed upon, including the specified amount and payment deadline. In the event of the buyer's default, the bank will guarantee the payment. Unfortunately, the implementation of L/C in Indonesia has faced criticism and issues due to the lack of rigid regulations governing its use. The regulations regarding L/C are briefly mentioned in Government Regulation No. 1 of 1982 and Bank Indonesia Circular No. 26/34/ULN, but these regulations do not fully accommodate the application of L/C in Indonesia. Based on these grounds, the author intends to examine the validity of L/C in Indonesia based on the prevailing regulations and discuss the resolution of L/C disputes in Indonesia, given the lack of specific regulations concerning such matters.